(untitled) (GEOmedia, 2015)
Un ponte normanno che versa in stato di totale abbando no nel contesto unico delle forre laviche ai piedi dell’Etna. Un topog rafo che, nonostante alcune difficoltà logistiche ne effettua il rilievo. An ancient norman bridge in disrepair at the foot of Etna, in Sicily. The project to restore the bridge needed a detailed scale model of the bridge and the surrounding area. The survey proved to be demanding due to the difficult conditions of the area: dense vegetation and steep terrain.